Epidemic Keratoconjunctivitis in Al-Ramadi City - Al-Sabti, Zeina M. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Epidemic keratoconjunctivitis (EKC) is a viral conjunctivitis caused by a group of adenoviruses. EKC is highly contagious and has a tendency to occur in epidemics.Objectives: The aim of this study is to evaluate the efficacy of fluorometholone(0.1%) eye drop in the management of viral EKC in Al-Ramadi city .Patients and methods: 300 patients were examined in the private clinic at Al-Nahrain Eye Specialty center from February 2009 to September 2011 and follow up of the patients extended from 3months to 12 months.Those patients were divided into two groups: first group includes 150 patients(95 males and 55 females, aged from 1 year to 65 years) was treated by cold compresses with lubricant eye drop without the use of fluorometholone eye drop.Second group includes 150 patients(80 males and 70 females, aged from1 year to 65 years) was treated by cold compresses with lubricant eye drop and fluorometholone (0.1%) eye drop.Results: Regarding the first group, this study showed that recovery without sequelae was noted in 63(42%) patients. Corneal subepithelial opacities were detected in 76(50.6%) patients, while 10(6.6%) patients developed conjunctival scarring, and only one (0.6%) developed conjunctival cyst.Data from the second group showed that 120(80%) patients recovered without complications, while 30(20%) patients developed subepithelial opacities and no one(0%) develop conjunctival scarring or conjunctival cyst.Conclusion: Use of fluorometholone eye drop in treatment of EKC : Alleviate the patient's symptoms, decrease the course of the disease and decrease the occurrence of subepithelial opacities.So it is recommended to use fluorometholone (0.1%) eye drop in the treatment of EKC.